Pengaruh Harga, Promosi, dan Kualitas Pelayanan Terhadap Keputusan Pembelian Kopi Kenangan Cabang Margacinta Kota Bandung - Aulia, Nurliana; Akbar, Ridho Riadi (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
The purpose of this study was to see how pricing, promotion, and service quality influenced purchasing decisions at Kopi Kenangan Margacinta Branch. This study employs quantitative methodologies with descriptive and verification approaches, utilizing both primary and secondary data. Using the Slovin algorithm, the researchers picked 100 respondents among 1,677,597 residents of Margacinta City Bandung. This study indicates that price, promotion, and service quality all have a significant impact on the purchasing decision of Kopi Kenangan. The statistics demonstrate that price has a considerable influence on purchase decisions, with a t-count value of 3.550 and a level of significance of 0.00. Sales promotion has a considerable influence on purchase decisions, as demonstrated by a t-value of 2.391 with a significance level of 0.00, as does service quality, as indicated by a t-value of 2.049 with a significance level of 0.00. These three criteria also have a substantial role in purchasing decisions, as evidenced by a p-value of 3,243 and a highly significant p-value of 0.000.